H-Point Standard Addition Method for Simultaneous Determination of Maneb and Zineb. Issue 1 (2009) - Kaur, P. P.; Gupta, U.
Abstract : The H-point standard addition method (HPSAM) has been applied for simultaneous determination of maneb and zineb using 1-(2-pyridylazo)-2- naphthol (PAN) as a reagent. Both maneb and zineb form wine red colored complex with PAN at pH 9.2 which are soluble in Triton X-100. Zineb and maneb can be determined simultaneously in the range of 0.414-3.446 µg mL -1 and 0.663-3.316 µg mL -1 respectively with satisfactory accuracy and precision. The proposed method has successfully been applied for the simultaneous determination of maneb and zineb in several synthetic samples, spiked water samples and crops